Transitioning from information sharing to knowledge services: unpacking the evolution of rural media within the context of media integration - Wang, Shujie; Li, Ning; Liu, Niwen; Habes, Mohammed (Springer, 2023)
TikTok, a short video-sharing platform, has captured a massive audience since its inception in 2016. This article explores the evolution of rural media in China, the burgeoning TikTok rural market, and the unique landscape of rural TikTok users. By investigating the development trajectory of TikTok and probing into the individual usage patterns, motivations, and preferences of rural TikTok users, this study aims to gain deeper insights into their distinct characteristics. Furthermore, this study employs two theoretical frameworks, the uses and gratifications theory and the media enjoyment theory, to analyze the causal relationship between Chinese TikTok rural users and their direct demands and satisfaction levels. Leveraging a combination of big data crawling and comprehensive questionnaire surveys, we provide data-driven perspectives on rural TikTok users’ experiences, motivations, and challenges. Our findings reveal that TikTok has become a compelling entertainment and social interaction source for rural users, aligning with its original positioning. The adaptability of TikTok’s content curation algorithms caters to diverse age groups, contributing significantly to user satisfaction. However, content quality and influencer representation disparities persist as challenges for rural TikTok users. This research offers valuable insights into the practical issues faced by rural TikTok users and presents recommendations for their enhanced engagement with the platform. By bridging the urban–rural digital divide, this study contributes to a more equitable media landscape in China and underscores the platform’s role in reshaping the dynamics of knowledge dissemination and entertainment consumption in the knowledge-based economy of the twenty-first century.